2006
DOI: 10.1366/000370206776342508
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Source Rock Origin by Chemometric Analysis of Fourier Transform Infrared—Attenuated Total Reflectance Spectra of Oil Petroleum: Evaluation of Aliphatic and Aromatic Fractions by Self-Modeling Mixture Analysis

Abstract: This study describes a new methodology for the interpretation of Fourier transform infrared (FT-IR) attenuated total reflectance (ATR) spectra of Algerian, Brazilian, and Venezuelan crude oils. It is based on a comparative study between a chemometric treatment and the classical one, which refers to indices calculation. In fact, the combined use of FT-IR indices and principal component analysis (PCA) has led to the classification of the studied samples in terms of geographic distribution. Quantitative analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…In order to obtain the proper resolution of the mixture data, user interaction is required to deal properly with features such as noise, peak shift, and instrument drift [41]. Some applications of SIMPLISMA have already been reported in the literature, e.g., on Fourier transform Raman spectra for the time resolved activation of hydrogen peroxide by a nitrile [30], analysis of oil petroleum [42], FT-IR microscopy spectra of a polymer laminate, and pyrolysis mass spectra of biomaterials (feedstock) [35,40]. The fitting of the SIMPLISMA results is calculated using the Relative Residual Sum of Squares (RRSSQ), square sum between the calculated and the original spectra.…”
Section: Curve Resolution Methodsmentioning
confidence: 99%
“…In order to obtain the proper resolution of the mixture data, user interaction is required to deal properly with features such as noise, peak shift, and instrument drift [41]. Some applications of SIMPLISMA have already been reported in the literature, e.g., on Fourier transform Raman spectra for the time resolved activation of hydrogen peroxide by a nitrile [30], analysis of oil petroleum [42], FT-IR microscopy spectra of a polymer laminate, and pyrolysis mass spectra of biomaterials (feedstock) [35,40]. The fitting of the SIMPLISMA results is calculated using the Relative Residual Sum of Squares (RRSSQ), square sum between the calculated and the original spectra.…”
Section: Curve Resolution Methodsmentioning
confidence: 99%
“…Peaks at 1600 cm −1 and 900-700 cm −1 indicate the presence of aromatic hydrocarbons. The presence of oxygenated functional groups was observed at 1800-1600 cm −1 (Abbas et al, 2006;White et al, 2016;Zhang et al, 2019). The peak assignments for functional groups in the variety of TMs are presented in Table 1.…”
Section: Chemical Composition and Structural Characterization Of Tms mentioning
confidence: 99%
“…Molecular level analysis of oil residues in the environment provides critical insight into changes in chemical composition of oil and the weathering processes responsible for these changes. Many researchers found that FTIR spectroscopy can be used as a rapid technique to characterize the chemical composition and weathering pattern (Permanyer et al, 2002;Abbas et al, 2006;White et al, 2016;Morrison et al, 2018). Literature review reveals that the level of TM contamination along the Qatar coast due to Gulf war oil spill had been assessed only two decades ago.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, spectral data treated using chemometric tools have allowed discrimination of oils from different origins, determination of reservoir compartments, assessment of oil biodegradation on the basis of the relative abundance of compound classes such as aliphatic, aromatic and polar species [13][14][15][16]. Structural and functional indices calculated from ratio of IR absorption bands areas were developed to characterize the chemical composition of crude oils.…”
Section: Introductionmentioning
confidence: 99%
“…The 700-900 cm À1 region was not considered because it was used to define substitution indices of aromatic rings [13]. The low absorption intensity in spectral zone at 3000-3100 cm À1 resulted in large errors.…”
Section: Introductionmentioning
confidence: 99%